Education and technology : key issues and debates - Selwyn, Neil (London, England : Zed Books, 2021)
"What does the future hold for digital technology and education? What can be learnt from the history of technology use in education? Does digital technology make education more individualized? Will it eventually replace the school, university and teacher? In a thoroughly revised edition of this successful book, Neil Selwyn takes a critical look at some of the major current debates and controversies concerning digital technologies and education. Focusing on the social as well as the technical aspects of these issues, Selwyn addresses fundamental but often unvoiced questions about education and technology. Over the course of eight chapters, the book gives careful thought to the people, practices, processes and structures behind the rapidly increasing use of technologies in education, with an emphasis on the implications of digital technologies for individuals and institutions. Brand new chapters on trends in AI and 'big data' driven automation of education, and the future(s) of education and technology are included. This edition also features new sections exploring 'post-digital' perspectives, personalized learning, digital labour, and the impending need for sustainable forms of digital education. The book focuses attention on the connections between recent technology developments and broader changes in education practice, education policy and education theory over the past few decades. It also challenges us to reflect on future directions and controversies for education in the (post)digital age. Expanded study questions, annotated further reading and a new glossary of key terms are included to support readers. An updated companion website links to bonus chapters and audio recordings for further discussion"--
What do we mean by "education" and technology? -- Making sense of technology and educational change -- A short history of education and technology -- Technology and learning -- Technology and educational institutions -- Technology and teachers -- Artificial intelligence and the automation of education -- Education and technology: Looking to the future.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Educational technology -- Study and teaching -- United States; Educational technology -- Curricula -- United States; Internet in education -- United States; Teaching of a specific subject; Electronic books